Yerba mate as a novel inducer for fungal chlorogenate hydrolase production - Butiuk, Ana Paula (2015)
The potential of yerba mate (Ilex paraguariensis) to induce chlorogenate hydrolase (EC 3.1.1.42, CHase) activity in different fungal strains has been investigated. CHase was highly induced in mycelia of Aspergillus niger AKU 3302 grown in Czapek medium containing yerba mate extract as inducer. Different materials derived from yerba mate processing were examined as CHase activity inducers. All yerba mate samples produced CHase activity and a concentrated aqueous yerba mate extract was selected as the most convenient inducer. A response surface methodology was used to assess the simultaneous effect of inducer concentration and induction duration on enzyme production. The experimental design revealed that the optimum CHase production was achieved after long induction times (≥25 h) and low inducer concentrations (0.1–0.2% w/v, dry basis).